Impact of Pediatric Emergency Care Applied Research Network Rules on Admission, Cranial Computed Tomography and Skull X-ray Rates in a Central European Hospital. Issue 1 (January 2022) - Poyntner, Lukas; Simma, Burkhard
Abstract : Objectives: Mild head injury is a common cause of pediatric emergency department visits. Cranial computed tomography (CCT) is the diagnostic standard, although it involves inherent radiation risks. Pediatric Emergency Care Applied Research Network (PECARN) clinical prediction rules were developed to reduce the number of CCT scans. They provide a guideline for CCT use in mild head injuries, based on clinical parameters. Our study aims to evaluate the impact of PECARN rules on hospital admission and CCT rate in children with mild head injury. Methods: In this retrospective study, we investigated 729 children with mild head injury presenting in the pediatric emergency department between 2012 and 2016. We compared 2 groups, before and after implementation of PECARN criteria in clinical routine. Results: Of 729 included patients (417 male; 5.6 ± 4.8 years;) 380 were seen prior to implementation of the PECARN rules, compared to 349 patients afterwards. Overall admissions to the ward decreased significantly from 83.9% (n = 319) to 71.3% (n = 249) ( P < 0.001), a 31.3% reduction. Calculated from all pediatric admissions, the rate of patients with mild head injury fell from 6.0% to 4.3% ( P < 0.001). We recorded a nonsignificant decrease in the CCT rate, from 14.7% to 13.2% ( P = 0.555). No readmissions were recorded. Conclusions: Our results show a significant reduction in the rate of hospital admission following implementation of the PECARN rules in our hospital. Already low, the CCT rate did not change after implementation. The PECARN rules appear to be safe because no readmissions were recorded.